2011
DOI: 10.1007/s00345-011-0701-4
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler ultrasound imaging in varicoceles: is the venous diameter sufficient for predicting clinical and subclinical varicocele?

Abstract: Our findings support the hypothesis that clinical varicoceles can be predicted with high accuracy based only on the diameter of testicular veins using cut-point values of >2.45 mm in rest or >2.95 mm during Valsalva maneuver in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 19 publications
1
45
0
2
Order By: Relevance
“…The most widely accepted criterion is presence of multiple veins with a diameter[3.0-3.5 mm in conjunction with reversal of flow on color Doppler ultrasound [35]. In a recent study, Pilatz et al [36] found that clinical varicoceles can be predicted with high accuracy (sensitivity [80 %, specificity [80 %) based only on the diameter of testicular veins, using cut off values of 2.45 mm (at rest) and 2.95 mm (during the Valsalva maneuver) in the supine position. An implication of that study is that Doppler evaluation is not necessary to assess clinical varicoceles, because a B-scan of vein diameters predicts clinical varicoceles with high accuracy.…”
Section: Treatment Indications and Varicocele Managementmentioning
confidence: 99%
“…The most widely accepted criterion is presence of multiple veins with a diameter[3.0-3.5 mm in conjunction with reversal of flow on color Doppler ultrasound [35]. In a recent study, Pilatz et al [36] found that clinical varicoceles can be predicted with high accuracy (sensitivity [80 %, specificity [80 %) based only on the diameter of testicular veins, using cut off values of 2.45 mm (at rest) and 2.95 mm (during the Valsalva maneuver) in the supine position. An implication of that study is that Doppler evaluation is not necessary to assess clinical varicoceles, because a B-scan of vein diameters predicts clinical varicoceles with high accuracy.…”
Section: Treatment Indications and Varicocele Managementmentioning
confidence: 99%
“…A pencil probe doppler (9 MHz) is inexpensive tool that may be helpful in diagnosing varicocele. Examination should be carried out with the patient in standing position and a venous "rush" produced by the blood reflux should be heard under valsalva maneuver [43]. Although simple, this method was also shown to be positive in men harbouring subclinical varicocele [44].…”
Section: Diagnosis Of Varicocelementioning
confidence: 99%
“…26 In another study of 270 adult men, varicocele diag nosis was dependent upon an MVD of at least 2.45 mm at rest (sensitivity = 84%; specificity = 81%) or 2.95 mm during the Valsalva maneuver (sensitivity = 84%; specificity = 84%). 27 However, there is also evidence to suggest that reflux can occur in veins smaller than 2 mm in diameter. 28 In addition to its diagnostic role, MVD also has a prognostic role in adults.…”
Section: Vein Diametermentioning
confidence: 99%